ILF-neurofeedback in clinical practice: examining symptom change and performance metrics across diagnostic groups - Theis, Thomas; Bolduan, Ute; Seuß, Sigrid; Spallek, Johannes; Wandernoth, Bernhard; Mayer-Pelinski, René (Frontiers in Human Neuroscience, 2025)
IntroductionNeurofeedback (NF), particularly Infra-Low Frequency (ILF) Neurofeedback, is an emerging method of neuromodulation aimed at enhancing the brain’s self-regulation. It is a potentially powerful tool to complement the clinician’s toolbox, supporting the treatment of symptoms stemming from arousal regulation deficiencies. Despite the broad use and applicability of the arousal regulation model, there is a gap between its practical use and academic research. This study examines the effectiveness of ILF Neurofeedback across different diagnostic groups and explores whether subjective symptom changes correlate with objective performance measures.MethodsBetween 2015 and 2024, a study of 256 patients in an occupational therapy practice focused on comparing the influence of ILF Neurofeedback on different symptomatic groups. The groups were divided according to the ICD-10 F-codes for “F3—Mood Disorders” (MO), “F4—Neurotic, Stress-Related, and Somatoform Disorders” (NS), “F8—Developmental Disorders” (PD), and ‘F9—Childhood/Adolescent Behavioral Disorders’ (BE). Symptom tracking and the Continuous Performance Test (CPT) for assessing errors and reaction times were used to monitor progress before and after neurofeedback therapy.ResultsDiscriminant analysis showed significant symptom profile differences across diagnostic groups with an accuracy of 79%. A linear mixed model revealed consistent symptom reduction over Neurofeedback sessions, with a faster decline in early sessions. ILF Neurofeedback improved response times, reduced errors, enhanced discriminative ability, and increased caution, with no group differences. Correlation analysis showed that symptom tracking correlated with reduced commission errors and improved d-prime in the MO group, while in NS, it was linked to d-prime increase. In PD, symptom tracking correlated with correct responses and fewer omission errors; no significant correlations were found in BE.DiscussionThis study confirms that ILF Neurofeedback is equally effective across four diagnostic groups regarding self-report and performance. Symptoms significantly decreased during NF, with the fastest decline in the first 10 sessions. Performance improvements were seen in Continuous Performance Test measures, but symptom decline only correlated with performance in some groups. This suggests that subjective ratings and performance may be independent or depend on the diagnostic group. Further research with a control group is needed to explore ILF’s effects.